Carica papaya leaf ethanol extract effect on milk volume, β-casein gene (Csn2) expression, β-casein levels, and milk total protein levels - Yanti Herawati; Umi Kalsum; I Wayan Arsana; Lelly Yuniarti; Teguh Wahju Sardjono (Faculty of Pharmacy, Mahidol University, 2022)
The phytochemical compounds contained in papaya leaves are known to have a galactopoietic effect. This study aims to analyze the effect of ethanol extract of Carica papaya leaves on β-casein gene expression, βcasein levels, total protein, and milk volume. This in vivo was an experimental study including a posttest control group that was conducted on one control group and three treatment groups. Each group consisted of six lactating rats. The control group rats were given ordinary food, while the treatment group rats, D1, D2, and D3, were given ethanol extract of Carica papaya leaves with the dose of 0.95 mg, 1.9 mg, and 3.8 mg/200 g Body weight (BW)/day, respectively, from day 1 to day 13 of lactation. On day 14, all of the rats were sacrificed. Breastmilk volume taken from all breasts of lactating rats was measured individually in milliliters, β-casein gene expressions in the mammary tissues were measured using reverse transcription polymerase chain reaction (RT-PCR), while serum β-casein levels were measured using ELISA, and total protein was measured using bicinchoninic acid (BCA) protein assay. Statistical analysis was carried out using one-way ANOVA, Tukey test, and Games-Howell test at 95% confidence level. Milk volume, β-casein gene expression, β-casein levels, and total protein levels of all treatment rat groups were significantly higher than the control group (p<0.05). The increases of all parameters were consistent; the most effective dose was 1.9 mg/200g BW. Carica papaya leaf ethanol extract can increase milk volume, β-casein gene (Csn2) expression, β-casein levels, and total protein levels.